PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 019 LENGGADAI HULU - Wina Anggelina; Zetra Hainul Putra; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems of this research are a) in teaching and learning process, the teaching metode is not interesting, it focuses on one metode. b) the student’s motivation in learning science is low. c). In teaching and learning process, the students often move their chairs, so the situation in the class room is noise. d) in teaching the lesson, the teacher always stands up front of class, E) most of students are playing in teaching and learning process. The subject of this research is the grade IV SDN 019 Lenggadai Hulu that consists of 20 students. The object of this research is, the implementation of cooperative learning model make a match type in the science subject at class IV SDN 019 Lenggadai Hulu. The result of the research shows that the implementation of using cooperative learning model, make a match type in pre test are 7 students or (35 %) got high result (pass), 13 students or (65%) got low result (not pass). At the first cycle, there are 12 students (60%) having high result (pass). And 8 students (40 %) having low result (not pass). At the second cycle, there are 17 students (85 %) having high result (pass), and 3 students or (15 %) having low rresult (not pass). While, the result of research shows that the average of teaching activity at the first cycle is 77,85 % (good category), at the second cycle is 89,36% (very good category ). According to the research result, it can be concluded that using of cooperative learning model make a match type, the students can be motivated because the students active in teaching and learning process.so that, in teaching and learning science by using cooperative learning make a match type can increase science learning result at grade IV SDN 019 Lenggadai Hulu Kecamatan Rimba Melintang Kabupaten Rokan Hilir.Keywords: Cooperative Learning Model Make A Match Type, Science Learining Result